Information seeking behaviour factors: A measurement model - Mohd Nadzir, Maslinda; Salim, Juhana (2013)
Graduate students are active information seekers. Their experiences with information seeking range from novices to experts. Graduate students' understanding of the needed information and the different types of information sources accessible are essential for them to search for the required information effectively and efficiently. Previous studies concluded that insufficient knowledge about information seeking behaviour is one of the factors that contributed to failure in searching for useful information. This paper discuss about a study conducted to evaluate a measurement model of information seeking behaviour factors, which is a part of the methods used to develop Research Information Seeking Behaviour Model.The data was collected through survey method by using web-based questionnaire.The measurement model was validated using Structural Equation Modeling with AMOS 16.0. Eight factors were extracted from exploratory factor analysis and labeled as preliminary research needs, data research needs, printed information sources, electronic information sources, media information sources, library information search, electronic information search and information use.Results of the assessment of model fit showed that all the relevant measurements fit a value that exceeds the value recommended by previous researchers.In conclusion, the measurement model provides a reasonably good fit and suitable for the development of Research Information Seeking Behaviour Model.